Criminalità e sicurezza a Napoli: Secondo rapporto Crime and Security in Naples: Second Report - Giacomo Di Gennaro (Studi e Ricerche in Scienze Criminologiche, Giuridiche e Sociali, 2017)
In this second report on crime and security in Naples are addressed questions such as the determinants of a high propensity to illegal behavior although crime appears very risky, the appearance of youth-gangs and their peculiarities with respect to similar experiences in other countries, the correlation between social and economic vulnerability and the diffusion of an illegal credit market, the relationship between households' overindebtedness and their consumption behavior, the diffusion of an usury market where criminal organizations rise huge profits. Many changes have occurred in the deviant and criminal behaviors, and an appropriate response to all of them ask for a radical innovation in the policies to prevent, control and contrast crime. In our region, what might be perceived as a social damnation is actually the result of different factors that produce a sort of crime trap, such that the diffusion of illegal behaviors reduce legal opportunities making a criminal career more convenient.